The Development of a Nursing Documentation Model in the Accident and Emergency Unit, Maesai Hospital - Jakaom, Siriporn; Cheevakasemsook, Aree; Kusolvisitkul, Wilai (Journal of The Royal Thai Army Nurses, 2021)
This research and development aimed to develop a nursing document model at the Accident and Emergency Unit of Maesai Hospital. The samples comprised eighty seven previous nursing charts and new nursing charts, and seventeen professional nurses. Data were analyzed by descriptive statistics and t-test. The research findings were as follows. The problems of the nursing documentation revealed that the charting procedures were not based on nursing process, incomplete, incorrect, and discontinuous. The mean scores of the quality of nursing documentation after development was significantly higher than the prior at the level 0.01. The professional nurses’ satisfaction of the nursing documentation model after developing the model was also significantly higher than the previous one at the level 0.05.